THE HISTORY OF CIRCULATION IN THE SEA OF OKHOTSK DURING THE LATE PLEISTOCENE-HOLOCENE AS EVIDENCED BY FORAMINIFERS - Belyaeva N.V.; Burmistrova I.I. (My University, 1998)
Changes in composition of planktonic foraminifers in nine cores of bottom sediments obtained from different areas of the Sea of Okhotsk were analyzed in order to reconstruct the history of climate and circulation of the sea, and the influence of adjacent basins on the sea hydrology. The revealed changes in composition of benthic and planktonic foraminiferal assemblages throughout the cores showed that the Sea of Okhotsk hydrology recurrently changed during the last 60 ka. During this period, the temperature of surface and bottom waters in the central part of the Sea of Okhotsk was generally lower than at present and close to that characteristic now of the northern part of the sea. The warming episodes of surface and bottom waters occurred 50, 30, and 13.280 ka ago. Peculiarities in distribution of thermophilic planktonic species Globorotalia scitula appear to be related to changes in the regime of the Soya and Tsushima currents. Lower parts of the cores barren of this species and corresponding to the time interval of 60 to 13 ka suggest the lack of the warm water inflow from the Japan Sea. The appearance of G. scitula in cores at the level of 13 ka indicates the renewal of the activity of the Soya and Tsushima currents. Changes in the regime of these currents are related to sea-level fluctuations.
Keywords: Pleistocene; Holocene; Кайнозой::Четвертичная::Плейстоцен; Cenozoic::Quaternary::Holocene; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Голоцен